Young horse response on changing distance in free jumping combination - D. Lewczuk (Animal, 2008)
The aim of the present study was to verify the influence of distance between obstacles in combination for free jumping test on linear and temporal kinematic parameters of the jump. Investigated groups of halfbred stallions being prepared for 100 days performance test (two groups, 36 horses in total) were filmed on different distances between main doublebarre obstacle and last cross-pole in the jumping lane. Both groups of horses were filmed during their regular work in the same training centre 1 week before performance test. Jumping parameters were obtained on the same size of the obstacle. Data were analysed separately for both groups by analysis of variance. On the basis of the conducted study, it is possible to conclude that in the range of the most popular free jumping distance horses may use different jumping techniques to clear the jump. The shorter distances between last two obstacles in the jumping lane in the range of 6.8 to 7.1 m stimulate higher jumps; however, the reaction of horses was not exactly the same for all measured jumping parameters.